Holocene sedimentology and coastal geomorphology of Zakynthos Island, Ionian Sea: a history of a divided Mediterranean island - Avramidis, Pavlos; Koutsodendris, Andreas (Palaeogeography, palaeoclimatology, palaeoecology, 2017)
The island of Zakynthos is one of the most seismically active areas in the Mediterranean region because it is located very close to the convergent boundary between the African and Eurasian plates. Its evolution during the Holocene has been influenced by tectonic activity, catastrophic events and relative sea level changes. The scope of the present paper is to examine the Holocene palaeoenvironmental changes of the coastal areas of Zakynthos Island using a multidisciplinary approach, combining sedimentological and palaeontological data with 14C and OSL dating from four cores of a maximum depth of ~ 30 m. The integrated results reveal that sea level and tectonic activity have brought significant modifications in the coastal geomorphic settings of the island during the past ~ 10,000 yr B.P. The depositional environments and the palaeontological biofacies document four main geomorphological evolutionary stages of the island. We identified fully marine and lagoonal deposits with marine influence (before 4100 yr B.P.), as well as brackish and freshwater limnic depositional environments (around 4100 yr B.P. to present). The interpretation of our data indicates that Zakynthos island was separated into two main parts before the middle Neolithic period (around 7500 yr B.P.) with Vasilikos peninsula in the SE being isolated from the main island. The fact that Zakynthos Island was a divided Mediterranean island for a significant period of time in its prehistory is of great importance to understand better the archaeological landscapes of Zakynthos and the other Ionian Islands.